Pegylated-interferon-alpha treatment modulating the immune response of cytotoxic lymphocytes in cervical intraepithelial neoplasia - Letícia Montes Stark; Rosekeila Simões Nomelini; Marco Aurélio Trovó; Márcia Antoniazi Michelin; Eddie Fernando Candido Murta (Clinical and Experimental Obstetrics & Gynecology)
Background: Interferons are inducible secretory glycoproteins with immunomodulators, antiviral, antiangiogenic and antiproliferative effects. Evaluate the mechanisms responsible by regression of patients diagnosed with Cervical Intraepithelial Neoplasia (CIN) and treated with IFN-α, systemically and locally, by Interferon-α (IFN-α) receptor 1 (IFNR1) and IFN-α receptor 2 (IFNR2) and transcription factors STAT-1 (Signal Transducers and Activators of Transcription 1) and IRF-7 (Interferon Regulatory Factor 7), as well as the endogenous produced IFN-α by total (CD3+), Helper (CD4+), cytotoxic (CD8+) T lymphocytes and monocytes (CD14+). Methods: A prospective study was developed in which eighteen patients diagnosed with CIN II/III in treatment protocol with Peginterferon-α. Cells were evaluated using Real-Time and flow cytometry, and the data were analyzed using Kruskal-Wallis and ANOVA tests, considering p ≤ 0.05. Results: Eight patients obtained regression of the lesion, and ten did not obtain the regression. Patients who did respond positively to the treatment presented a CD8+ T lymphocyte with IFN-α increase when compared to patients who not responded positively. When analyzing CD8+ T lymphocytes during the stages of treatment in lesion regression, it is observed a significant IFNR1 (p = 0.0391) decrease in patients who did not achieve lesion regression. CD3 and CD14 data was not significant. Discussion: Immunomodulation by Interferon-alpha seems to depend on the systemic expression of IFN receptors. Our data suggest that patients who can respond to immunotherapy already have a pattern of IFN receptor expression in lymphocytes, which contributes to successful treatment.